Fodder banks: Problems and perceptions of participant pastoralists - Suleiman, H. (International Livestock Centre for Africa, 1984)
Dicusses techniques used by pastoralists in establishing fodder banks; includes seed bed preparation, manuring & weed control. Also discusses the grazing behaviour of cattle with ref. to the fodder bank, utilization of the bank, and factors affecting regeneration.